WASTEWATER TREATMENT IN INDUSTRY FROM A CTS PERSPECTIVE - Font Prieur, Daylen Yara; Yanelain Olmo, Yanelain; Arias Molina , Eliané; Lobelles Sardiñas , Gabriel Orlando (Revista Minerva, 2022)
In the way of approaching wastewater treatment, three fundamental stages can be distinguished: primary, secondary and tertiary stage. At first (prior to the 1980s), treatment technologies applied to wastewater were not very effective. Due to malfunctioning technologies, a high content of these wastewater affected both the environment and humanity, leaving these technologies out of service over time. At present, awareness of this situation is beginning, considering a whole range of possible technologies (filtration, sedimentation), all of them valid depending on the characteristics whose wastewater is going to be treated, and the discharge requirements. The following research is based on the study of wastewater treatment coupled with its technological progress to date with a Science Technology Society approach.